Parental plasma concentrations of perfluoroalkyl substances and In Vitro fertilization outcomes. (15th January 2021) - Ma, Xueqian; Cui, Long; Chen, Lin; Zhang, Jun; Zhang, Xiaohui; Kang, Quanmin; Jin, Fan; Ye, Yinghui
Abstract: Perfluoroalkyl substances (PFAS) are known to be endocrine-disrupting compounds, but are nevertheless widely used in consumer and industrial products and have been detected globally in human and wildlife. Data from animal and epidemiological studies suggest that PFAS may affect human fertility. This led us to consider whether maternal or paternal plasma PFAS had effects on in vitro fertilization (IVF) outcomes. The study population consisted of 96 couples who underwent IVF treatment in 2017 due to tubal factor infertility. The concentrations of 10 PFAS in blood samples from both male and female partners were measured. Poisson regression with log link was performed to evaluate the association between the tertiles of PFAS concentrations and numbers of retrieved oocytes, mature oocytes, two-pronuclei (2 PN) zygotes, and good-quality embryos, while multiple linear regression models were used to investigate the correlation between plasma PFAS and semen parameters. Multivariable logistic regression was used to evaluate the association between the tertiles of PFAS concentrations and clinical outcomes. It was found that maternal plasma concentrations of perfluorooctanoic acid (PFOA) were negatively associated with the numbers of retrieved oocytes ( p trend  = 0.023), mature oocytes ( p trend  = 0.015), 2 PN zygotes ( p trend  = 0.014), and good-quality embryos ( p trend  = 0.012). Higher paternal plasma PFOA concentrations were found to be significantly associated with reduced numbers of 2 PN zygotes ( p trend  = 0.047). None of the maternal or paternal PFAS were significantly associated with the probability of implantation, clinical pregnancy, or live birth. To our knowledge, the present study is the first to assess the association between parental exposure to PFAS and IVF outcomes. Our results suggest the potential reproductive effects of PFAS on both men and women, and that exposure to PFAS may negatively affect IVF outcomes. Future studies, particularly with large sample size cohorts, are needed to confirm these findings. Graphical abstract: Image 1 Highlights: We show the effect of parental exposure to PFAS on IVF outcomes. Maternal PFOA is negatively associated with the numbers of oocytes, 2 PN and embryos. Higher paternal PFOA levels was associated with reduced numbers of 2 PN zygotes. Abstract : PFAS may affect human fertility. Maternal or paternal plasma PFAS concentrations, especially PFOA, were found to be related to intermediate IVF outcomes.